Electromagnetic brain imaging based on standardized resting-state networks - Xu Lei (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
We have recently proposed a electromagnetic brain imaging based on multiple fMRI spatial priors: NEtwork-based SOurce Imaging (NESOI) [Lei et al. "fMRI Functional Networks for EEG Source Imaging," Human Brain Mapping, vol. 32, pp. 1141-1160, 2011]. In our previous method, the spatial priors is extracted from the fMRI dataset on the same subject within the same paradigm. In this paper, we present a resting-state NEtwork-based SOurce Imaing (rsNESOI), which includes fMRI priors without extra fMRI scan. While simultaneous electroencephalogram (EEG) recording within fMRI scanner is available currently, rsNESOI is more convenient for EEG source reconstruction. The real data test suggests that rsNESOI is distinctly valuable in improvement of distributed source localization in contrast to the previous methods.